Pengaruh Bentuk Geometri terhadap Laju Korosi Baja Karbon dalam Larutan NaCl 3,5% - Rudi Hartono; Amat Umron; Utdin F Amali (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
The geometry of metal components is an important factor influencing corrosion behavior, particularly localized corrosion. This study aims to analyze the effect of geometric variations on the corrosion rate of carbon steel through a simulated laboratory experimental approach. Carbon steel specimens were fabricated with three different geometries, namely flat surface, sharp-edged surface, and crevice geometry. Corrosion testing was conducted using immersion and potentiodynamic polarization methods in a 3.5% NaCl solution. The analyzed parameters included mass loss corrosion rate, corrosion potential, and corrosion current density. The results showed that crevice specimens exhibited the highest corrosion rate, followed by sharp-edged specimens, while flat surfaces demonstrated the best corrosion resistance. This behavior is attributed to the formation of differential aeration cells and non-uniform current density distribution caused by geometric variations. These findings highlight the importance of considering geometric design in corrosion mitigation strategies for metal components.